Color change of some aesthetic dental materials: Effect of immersion solutions and finishing of their surfaces - Elizabeth Sarkis (Saudi Dental Journal)
Objectives: The purpose of this research was to evaluate the color change of five aesthetic dental materials, before and after immersion in distilled water and blue food color solution for 7 and 21 days, and to study the effect of finishing the surfaces on any color change. Methods: Disc shaped samples of five types of light curing composite (A2) (n = 10 samples/composite) were prepared and all samples were light-cured with a Plasma Arc light cure unit for ten seconds. One side of each sample disc was finished and polished with a Super-Snap system all samples. After 24 h, color measurements of each sample were conducted using a digital spectrophotometer. Five sample discs from each composite group were immersed in 30 ml of food color solution for 7 and 21 days, while the remaining five sample discs were immersed in 30 ml of distilled water as a control. Color measurements were repeated for all samples at 7 and 21 days after immersion. The color changes were statistically analyzed using t-tests within the same group. A result was considered statistically significant at α = 0.05. Results: The color differences (ΔE) ranged from 0.4 to 4.66 and statistically significant differences on the finished and unfinished surfaces were observed after immersion in the food color solution for 7 days. No significant differences were found in any group after immersion in the food color solution for 21 days. The Tetric EvoCeram and Arabesk groups showed less color differences after 7 and 21 days than other composites. Conclusion: Finished composite surfaces showed less coloration than unfinished surfaces after 7 days, but all surfaces (finished and unfinished) were highly colored for all composite types after 21 days. Keywords: Color stability, Dental restoration, Composite, Color change, Surface finishing